Patient Satisfaction with Drug Information Services at X Cilegon Pharmacy in the Period June–July 2024 - Fitri Dwi Wijayanti; Meilani, Nur Afifah (Jurnal Kesehatan dan Kedokteran, 2025)
Satisfaction with using pharmacy services is the attitude of consumers in determining the final direction and goal in the process of understanding the correct use of medicines or purchasing a medicinal product, so that patient satisfaction using pharmacy services can be used as a benchmark to see how much satisfaction the patient has with the services provided (Hasyim , 2019). The aim of this research is to determine the level of patient satisfaction with drug information services at the Cendana Cilegon Pharmacy in the period June – July 2024. This research uses a quantitative descriptive research design. Sampling technique Stratified Random Sampling and there were 141 respondents. The samples in this study were patients or families of patients who bought medicine without a doctor's prescription at the Cendana Cilegon Pharmacy. Data collection was carried out by giving questionnaires to respondents. The data obtained from the questionnaire calculated the average percentage of satisfaction and categorized it. The research results show that patient satisfaction is based on the service quality dimension on the reliability dimension (reliability) 87% very satisfied category, responsiveness dimension (responsiveness) 88% very satisfied category, guarantee dimension (assurance) 90% very satisfied category, empathy dimension (empathy) 85% very satisfied category, and the physical evidence dimension (tangible) 81% of the category is very satisfied. The research results show that the average patient satisfaction value is 86% with the very satisfied category, which means that patients are very satisfied with the drug information services at the Cendana Cilegon Pharmacy.